A universidade, a história e o historiador : o itinerário intelectual de Francisco Iglésias - Alessandra Soares Santos (2013)
This thesis sought to, trough the study of the Francisco Iglésias intellectual itinerary between 1940 and 1990, recover the historical dynamics that had led to institutionalization of historical knowledge as a social science inside the university. We questioned the historian métier, with their notions and practices, inside the Brazilians universities in order to have a better understanding of what it means to write history in this “place”, after all, his objects, his methods and his techniques came from there. Besides, we tried to comprehend how Francisco Iglésias has incorporated the “discourse on language” of university historical knowledge and how these efforts had influenced his writings and his relationships with the historian’s community.